The Instagram as a Tool for Implementation of Social Crm (Customer Relationship Management) Study on Tourism in Lamongan Regency (Wisata Bahari Lamongan and Maharani Zoo) - B, Muh Ridwan (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2024)
Advances in technology and communication today have an impact on changes in the Industrial Revolution, including the Tourism Industry. The use of computers and the Internet of Things (IoT) in the tourism industry currently has an important role, which can include many ways, one of which is contact with customers. Customer Relationship Management (CRM) is a business strategy that integrates business processes that are directly related to consumers (marketing, sales, and services) with business people, business processes, and supporting technology to get customer retention [7]. Instagram is one of the social media that has a wide reach and can be accessed easily by anyone. In addition, Instagram is also available on mobile devices and makes Instagram one of the social media that has many users. The Lamongan Tourism and Culture Office has the responsibility to introduce tourist attractions in Lamongan. Lamongan Regency has two tourist icons that are well known by the public, both the Lamongan community itself and people from outside the Lamongan area, namely Lamongan Marine Tourism and Maharani Zoo. Instagram can be used as a Social CRM tool so that it has an impact on increasing tourist visits to Wisata Bahari Lamongan and Maharani Zoo.